Engineered Plasmonic and Fluorescent Nanomaterials for Biosensing, Motion, Imaging, and Therapeutic Applications - Esporrín-Ubieto, David (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.